Onychomycosis in patients with chronic leg ulcer and toenail abnormalities - Joana Cabete; Célia Galhardas; Margarida Apetato; Sara Lestre (Sociedade Brasileira de Dermatologia, 2015)
Nails have a limited number of reactive patterns to disease. Accordingly, toenail changes of different etiologies may mimic onychomycosis. OBJECTIVE To determine the prevalence of toenail onychomycosis among patients with leg ulcer and toenail abnormalities attending a dermatology clinic. METHODS A cross-sectional study was conducted through the analysis of clinical records and results of mycological examination. RESULTS A total of 81 patients were included, with a median age of 76.0 years. Most ulcers were of venous etiology, followed by those of mixed and arterial pathogenesis. The mycological evaluation confirmed the diagnosis of onychomycosis in 27.2% of the patients. The etiologic agent was a dermatophyte in 59.1% of isolates in nail samples, while Trichophyton interdigitale was the most frequent fungal species (40.9%). CONCLUSIONS Most toenail abnormalities in patients with chronic leg ulcer were not onychomycosis. This study highlights the importance of systematic mycological examination in these patients, in order to avoid overtreatment with systemic antifungals, unnecessary costs and side effects.